Endogenous environmental policy when pollution is transboundary - Joachim Fünfgeld; Günther G. Schulze (University of Freiburg, Department of International Economic Policy (iep), 2011)
We analyze the formation of environmental policy to regulate transboundary pollution if governments are self-interested. In a common agency framework, we portray the environmental policy calculus of two political supportmaximizing governments that are in a situation of strategic interaction with respect to their environmental policies, but too small to affect world market prices. We show how governments systematically deviate from socially optimal environmental policies. Taxes may be too high if environmental interests and pollution-intensity of production are very strong; under different constellations they may be too low. Governments may actually subsidize the production of a polluting good. Politically motivated environmental policy thus may be more harmful to the environment as compared to the benevolent dictators' solution. In other cases it may enhance environmental quality and welfare beyond what a benevolent government would achieve.
Keywords: Q58; F5; 330; political economy; environmental policy; transboundary pollution; common agency; strategic interaction